Creative and Innovative Language Teaching - Tono Suwartono; Irma Herawati; Dwi Suweni (Prodi PBA Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2022)
Creativity and innovation in language teaching are two significance elements which mutually support the achievement of language teaching goals. The success of language teaching depends on both the material presented and the presentation technique done by the teachers to their learners. In this case, the material is prepared in accordance with the provisions set out in the curriculum by paying attention to the content that is appropriate to the context in order to achieve the teaching target. Creativity in the preparation of teaching materials and contents is needed to make it easier for students to follow each stage of teaching. In addition to the creativity in the preparation of materials, creativity and innovation in delivering the materials are also obligatory parts. The creativity and innovation of teachers in delivering can be done by various teaching activities that seek to generate students’ interest in teaching, creative power, and students’ innovation power. From this, teaching plans that lead to students’ activities, creativity, and innovations become crucial charts that must be prepared by teachers before starting teaching activities in the classroom. Thus, this article presents some ways to create a creative and innovative language teaching.